Direct synthesis of substrate-independent nanoparticles for antibacterial application. (23rd July 2021) - Ye, Wei; Wang, Nan; Wang, Lingren; Liu, Sen; Zhang, Chao; Liu, Jingjing; Xin, Jiang; Ding, Hongyan
Abstract: In the present study, we designed a substrate-independent antimicrobial nanoparticle (SNP) via self-assembly of poly (acrylic acid) (PAA) and poly (diallyl dimethyl ammonium chloride) (PDDA). The prepared nanoparticle, with a cube structure, as revealed by scanning electron microscope (SEM), maintained structural integrity even after extensive washing. In addition, the SNP was endowed with substrate-independent adhesive affinity to various surfaces by carbodiimide reaction owing to the carboxyl group of PAA. The results of blood compatibility and cytocompatibility demonstrated that the SNP had a limited effect on blood coagulation and cell proliferation. The results of antibacterial tests indicated that the SNP exhibited significant inhibition ability for both gram-negative and gram-positive bacteria, reducing cell amount by 97.2% and 98.2% within 24 h for Escherichia coli and Staphylococcus aureus, respectively. The hemocompatibility and cytocompatibility were attributed to the introduction of carboxyl group, and the significantly antimicrobial property was ascribed to the introduction of PDDA. Furthermore, the SNP maintained outstanding long-term antimicrobial property. In general, it was believed that the designed SNP probably showed potential for applications in various biological and clinical fields.